POTENTIAL OF COMMUNITY BASED MANGROVE ECOWISATA DEVELOPMENT IN THE BAKAU BESAR LAUT VILLAGE SUNGAI KUNYIT SUBDISTRICT MEMPAWAH REGENCY - Rinda, Rinda Rinda; Soetignya, Widadi Padmarsari; Sirojul, Ahmad Mulyadi (Jurnal Sains Mahasiswa Pertanian, 2020)
ABSTRACTThis study aims to determine the potential of mangrove ecotourism in the Bakau Besar Laut Village area, know the suitability of mangrove ecotourism in the Bakau Besar Laut Village area, know the community perceptionof the Bakau Besar Besar Village of the development of ecotourism community-based mangrove. This research was conducted from September 2018-January 2019. The method used in sampling the potential of this mangrove forest is the purposive sampling method to determine the observation station, while the perception data collection is done by interviewing the community and visitors whose sample is determined by the proportional random sampling method. The results of the study found the potential of mangrove resources for ecotourism development consists of 8 types of mangroves and included in the conditional category to be used as ecotourism areas. Other potentials there are a variety of potential mangrove fauna in the form of monitor lizards, storks, kepah, crowak and shot fish that indicate the area has a value suitable to be managed as an ecotourism area. The availability of facilities and infrastructure is sufficient to support tourism activities. The Bakau Besar Laut has an ecotourism suitability index that is very suitable to be developed as an ecotourism area with suitability values ranging from 82-86.6%. And the carrying capacity of the area in the village of Bakau Besar Laut is only able to accommodate tourists as many as 40 people / day, so that the mangrove forests of the Bakau Besar Laut have the potential to be developed as an ecotourism area. Mangrove forests in the Bakau Besar Laut Village have ecotourism potential that can be seen from the perception and participation of the community in utilizing the habitat and function of mangrove forests as ecotourism areas and the community contributes to the management of mangrove ecotourism.Key words: Regional Carrying Capacity, Public Perception